English – Indonesian Passive Sentences in Cookbook - Ekasani, Kadek Ayu; Mas Indrawati, Ni Luh Ketut (e-Journal of Linguistics; Vol 14 No 1 (2020): e-jl January, 2020)
This research focuses on the English-Indonesian passive sentence in cookbook. The aim of this research is to find out how the English passive sentence translated into Indonesian passive one cookbook. The data source was taken from English cookbook entitled The Essential Book of Sauces & Dressings written by Lowery, et.al and published by Periplus, Singapore and the translation into Indonesian entitled “ Saus dan Dressing yang esensial ” translated by Hadyana P. and published by Periplus, Indonesia. The methods of collecting data are observation and documentation. Scintific article tends to use passive sentence rather than active one. This is intended to show the product and disappear the doer. In doing the works, the translator translated English passive voice into Indonesian passive voice in several ways. The results show in English cookbook found some passive constructions which are translated also into passive construction in TL. The passive construction in English cookbook are in the form of present tense (is/are + V past participle), modal passive (modal + be + V past participle), present perfect tense (has + been + V past participle). The translation in Indonesian are translated into passive construction by using verbs added by prefix di -, active construction with active verbs, and verbs added by prefix ter -.